ANTIMICROBIAL ACTIVITY OF Echinops kebericho AGAINST HUMAN PATHOGENIC BACTERIA AND FUNGI - Ameya, Gemechu; Gure, Abdella; Dessalegn, Engida (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
a well known endemic medicinal plant in Ethiopia and is traditionally used to treat both infectious and non-infectious diseases. The aim of this study was to evaluate antibacterial and antifungal activities of water, ethanol and methanol based crude extracts of E. kebericho Mesfin against selected human pathogenic bacteria and fungi. Materials and methods: Crude extracts of E. kebericho Mesfin were prepared by maceration method. Disc diffusion assay of the extracts was carried out in four different concentrations against three different bacterial species and two clinically isolated fungal species. Agar dilution method was used to determine minimum inhibitory concentration, minimum bactericidal and fungicidal concentrations of the extracts. Results: Water based extracts exhibited the lowest antimicrobial activity when compared the ethanol and methanol based extracts (P< 0.05). Among the tested microorganisms, S. aureus, C. albicans and A. flavus were the most sensitive to alcohol based extracts. The minimum inhibitory concentration of the alcohol based extract ranged from 3.12 to 25μg/ml while those of the water based extracts were 100μg/ml and above. The lowest bactericidal and fungicidal concentrations of the ethanol and methanol based extracts were observed to be 6.25μg/ml against S. aureus and C. albicans and 37.5μg/ml against E. coli. Conclusions: The traditional use of E. kebericho by local people in treating various types of infectious and non-infectious diseases was supported by this study. Antimicrobial activity of the medicinal plant varied with those of extraction solvents and against tested microorganisms.